The Influence of Electronic Word of Mouth On the Purchase Decision of Product X Beauty Users - Auliyaa Nurul Aziizah; Meita Santi Budiani (Entrepreneurship Faculty, Universitas Garut, 2022)
Implementing social distancing caused consumers to take care of their beauty and body care because they had more time at home, resulting in increased purchasing decisions for beauty care products. Purchase decisions have five aspects: need recognition, search for information, alternative evaluation, purchase decision, and post-purchase behavior. In the search for Information process, electronic word of mouth is the most helpful information because it is independent and has relevant information for consumers. This study aimed to see the effect of electronic word of mouth on purchasing decisions of the user of beauty products X. This study used associative quantitative research techniques. One hundred participants were selected purposively to be the samples of the study. The data were taken using a Likert scale questionnaire as a research instrument and analyzed using simple linear regression analysis with SPSS 25.00. The analysis result obtained a significance value of 0.00 < 0.05. Therefore, the Electronic Word of mouth influences the Purchase Decision variable of the user of beauty product X